PENERAPAN MODEL PBL MELALU LKM TEKS “TAK MUAT LAGI” UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK DAN KALIMAT TRANSITIF DAN KALIMAT INTRANSITIF SISWA KELAS IV SD - Kadhita Chandra Hapsari; Nur Aini Aulia Rizqi; Oshinky Diva Karisma Septiara; Ratna Erviana; Panca Dewi Purwati (STKIP Subang, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) model through a student worksheet (LKM) based on the text “Tak Muat Lagi” and to analyze its improvement on fourth-grade students’ listening skills and understanding of transitive–intransitive sentences. Using a mixed-methods approach in a two-cycle Classroom Action Research (CAR) design, each cycle consisted of planning, action, observation, and reflection. The subjects were 25 students. Data were collected through listening tests, transitive–intransitive sentence tests, observation sheets, student questionnaires, and documentation. The results show an increase in student learning outcomes. In Cycle I, the average score was 72.4 with 64% mastery. After improvements in Cycle II, the average score rose to 86.8 with 92% mastery. Student responses were positive, with 88% finding the learning engaging and easy to understand, and 84% feeling more confident in using transitive and intransitive sentences. Thus, implementing PBL through contextual worksheets effectively improves listening skills and sentence structure mastery.